Real-time ocean wave prediction in time domain with autoregression and echo state networks - Holand, Karoline; Kalisch, Henrik (Frontiers in Marine Science, 2024)
This study evaluates the potential of applying echo state networks (ESN) and autoregression (AR) for dynamic time series prediction of free surface elevation for use in wave energy converters (WECs). The performance of these models is evaluated on time series data at different water depths and wave conditions, including both measured and simulated data with a focus on realtime prediction of ocean waves at a given location without resolving for the surrounding ocean surface, in other words, short-time single-point forecasting.The work presented includes training the models on historical wave data and testing their ability to predict phase-resolved future surface wave patterns for short-time forecasts. Additionally, this study discusses the feasibility of deploying these models for extended time intervals. It provides valuable insights into the trade-offs between accuracy and practicality in the real-time implementation of predictive models for wave elevation, which are needed in wave energy converters to optimise the control algorithm.